2017
DOI: 10.1002/2016jd026374
|View full text |Cite
|
Sign up to set email alerts
|

Sunshine duration and global radiation trends in Italy (1959–2013): To what extent do they agree?

Abstract: Two Italian homogenized data sets of sunshine duration (SD) and global radiation (Eg↓) relative anomalies are used to investigate to what extent these two variables agree with respect to their temporal evolution. They are compared for northern and southern Italy over the period 1959–2013. Both under all‐sky and clear‐sky conditions, the SD records tend to show a shorter and less intense decrease until the 1980s (“global dimming”) with respect to the Eg↓ ones, while there is a better agreement in the subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 100 publications
4
10
1
Order By: Relevance
“…A direct comparison of observed‐derived R s (with 44 pairs of stations) reveals consistent trends during the periods of dimming (−1.11 W/m 2 per decade versus −1.38 W/m 2 per decade from 1961 to 1980) and brightening (1.51 W/m 2 per decade versus 1.47 W/m 2 per decade from 1980 to 2009) in Europe (Figure b and Table ), further suggesting that SunDu‐derived R s data can accurately reproduce the observed trends in Europe from 1961 to 2009. This seems to be inconsistent with Manara et al (), who showed substantial differences in the trends between the SunDu and R s in Italy during the dimming period but similar trends during the brightening period. Simultaneously, they considered that the observed SunDu and R s data have different sensitivities for different climatic conditions, especially in the dimming period.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…A direct comparison of observed‐derived R s (with 44 pairs of stations) reveals consistent trends during the periods of dimming (−1.11 W/m 2 per decade versus −1.38 W/m 2 per decade from 1961 to 1980) and brightening (1.51 W/m 2 per decade versus 1.47 W/m 2 per decade from 1980 to 2009) in Europe (Figure b and Table ), further suggesting that SunDu‐derived R s data can accurately reproduce the observed trends in Europe from 1961 to 2009. This seems to be inconsistent with Manara et al (), who showed substantial differences in the trends between the SunDu and R s in Italy during the dimming period but similar trends during the brightening period. Simultaneously, they considered that the observed SunDu and R s data have different sensitivities for different climatic conditions, especially in the dimming period.…”
Section: Resultscontrasting
confidence: 85%
“…Simultaneously, SunDu is almost free from influences of instrument replacement (Stanhill & Cohen, ). Even though, SunDu data do not provide a direct estimate of R s and have the different sensitivity of atmospheric turbidity changes, compared with R s observations, they are still a good proxy for variations of R s (Manara et al, ). Moreover, existing studies have shown that SunDu‐derived R s estimates roughly depict long‐term variability in R s almost without the problems associated with early radiometry mentioned above (K. Wang, ; K. Wang et al, ) and reflect to some extent impacts of both aerosols and clouds (Tang et al, ; K. Wang, Dickinson, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As the resultant trends of SD and DTR, compared with the SSR trend, diverged in the second period for São Paulo, in all sky conditions, caution might be taken when those variables are used as proxies to downward surface solar radiation in the context of dimming and brightening analyses. This study revealed that different factors may act on each variable, leading to a distinct behavior, as also mentioned by Manara et al (2017).…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, the surface observed sunshine duration data that were used for estimating DSR (Wang, 2014;Yang et al, 2006) were not available over the TP until the 1960s. Regardless, the statistical model can hardly capture the low aerosols' influence on surface solar radiation by sunshine duration because sunshine duration has a lower sensitivity than DSR to atmospheric turbidity changes that is estimated by aerosol optical depth (AOD) (Manara et al, 2017). Thus, considering that remote sensing has been developed for several decades, it provides a valuable opportunity to employ satellite observations to monitor spatiotemporal variations at regional scales.…”
Section: Introductionmentioning
confidence: 99%